'Do nurses really do that’? An exploratory study of students - Topola, Leanne; Miller, Kathleen (My University, 2021)
Background: Health care needs are changing, requiring nurses to assume leadership roles and engage in political activism to impact health system transformation. Nursing education socializes students to the profession, as this is where they begin to develop their professional identity. For these reasons' educators must begin to explore student perceptions of the role of the registered nurse given the emphasis on leadership and health care transformation and question if students want to assume these roles. Objectives: To identify first- and fourth-year baccalaureate nursing student perceptions of the role of the nurse and analyze their willingness to participate in roles that embody leadership and political action.
Keywords: perceptions; political action; leadership; nursing students